2010
DOI: 10.1007/s00216-010-3759-8
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectral imaging of single cancer cells: probing the impact of sample fixation methods

Abstract: Raman spectroscopy has proven its potential for the analysis of cell constituents and processes. However, sample preparation methods compatible with clinical practice must be implemented for collection of accurate spectral information. This study aims at assessing, using micro-Raman imaging, the effects of some routinely used fixation methods such as formalin-fixation, formalin-fixation/air drying, cytocentrifugation, and air drying on intracellular spectral information. Data were compared with those acquired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 18 publications
4
63
0
Order By: Relevance
“…16,17 Thus, the potential applications extend beyond disease diagnostics to the label free in vitro screening of cytological processes, such as drug or nanoparticle uptake and mechanisms of interaction, and toxicology. 16,[18][19][20] There has been a wide range of studies to date demonstrating the potential of Raman micro spectroscopy to map live and fixed cells with subcellular resolution, [21][22][23][24][25] profile the distribution of anticancer agents [26][27][28][29][30] and nanoparticles in cells 16,31,32 and monitor subcellular processes 33 and toxicological responses. [34][35][36][37] Fundamental to the development of applications of Raman micro spectroscopy for disease diagnostics as well as analysis of cytological processes is an understanding of the variability of the spectral signatures across the subcellular environment, their potential for differentiation of cell phenotype or diseased state, and their sensitivity to external perturbation, such as viral infection, radiation damage, or chemical stress due to, for example, toxic or chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Thus, the potential applications extend beyond disease diagnostics to the label free in vitro screening of cytological processes, such as drug or nanoparticle uptake and mechanisms of interaction, and toxicology. 16,[18][19][20] There has been a wide range of studies to date demonstrating the potential of Raman micro spectroscopy to map live and fixed cells with subcellular resolution, [21][22][23][24][25] profile the distribution of anticancer agents [26][27][28][29][30] and nanoparticles in cells 16,31,32 and monitor subcellular processes 33 and toxicological responses. [34][35][36][37] Fundamental to the development of applications of Raman micro spectroscopy for disease diagnostics as well as analysis of cytological processes is an understanding of the variability of the spectral signatures across the subcellular environment, their potential for differentiation of cell phenotype or diseased state, and their sensitivity to external perturbation, such as viral infection, radiation damage, or chemical stress due to, for example, toxic or chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of the sub-cellular structures such as the nucleus, cytoplasm and mitochondria can be achieved 23 and chemical maps can be constructed giving information about the distribution of differentiating molecules such as proteins 24 . However, these have been performed on chemically fixed cells and it has since been demonstrated that chemical fixation induces significant changes to the biochemistry of the cell 25,26 . Ultimately, if subtle changes in metabolism due to for example chemotherapeutic agents, toxicants, or radiation are to be discerned, live cells should be studied.…”
Section: Introductionmentioning
confidence: 99%
“…16 Using hierarchical cluster analysis and principal components analysis (PCA) on individual Raman spectra randomly selected form the nuclear regions of single cancer cells, Draux and co-workers have shown that formalinfixation and cytocentrifugation are sample preparation methods that have little impact on the biochemical information as compared to living conditions. 17 Although the chemical fixation is a possible confounding variable in the differentiation and classification analysis of the spectra acquired from the normal and diseased eye samples, its impact on the analysis is limited in nature since all samples were processed under identical conditions.…”
Section: Spectral Data Processingmentioning
confidence: 99%